A permanent campaign? Tweeting differences among members of Congress between campaign and routine periods. Issue 4 (2nd October 2019) - Vasko, Vidar; Trilling, Damian
ABSTRACT: This article investigates whether the notion of a "permanent campaign" characterizes politicians' Twitter use by analyzing 285, 456 tweets by Members of Congress during and after the 2016 US elections. We distinguished a campaign period, a lame duck period, and a routine period. The inclusion of a lame duck period is novel in studies on social networking sites and allows for more precise conclusions. In the routine period, politicians focused more on hard news, put more emphasis on domestic than foreign content on the country level, had a higher level of negative sentiment and published more tweets, whereas in the campaign period positive sentiment was higher. Additionally, we found large differences in politicians' tweeting behavior between the lame duck and routine period. We conclude that the notion of a 'permanent campaign' does not appropriately describe political campaigning on Twitter, but that the exact differences are still poorly understood, as empirical findings do not align well with previous literature.